CORAL CARBONATE PRODUCTION DURING THE PALEOCENE: INSIGHTS FROM THE MAIELLA MASSIF (PENNAPIEDIMONTE, CENTRAL ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
The succession of the Maiella massif is analyzed, focusing on the colonial-coral bearing deposits occurring just below and immediately above the Cretaceous/Paleogene boundary. The Upper Cretaceous material is dominated by rudists and larger benthic foraminifera with a significant contribution from colonial corals. In the Lower Paleocene, the first two groups are absent and colonial corals dominate the skeletal assemblage. This supports the hypothesis of a good recovery of colonial corals carbonate production following the end Cretaceous extinction and their overall resilience. Similar to modern reefs, Lower Paleocene bioconstructions have a framework dominated by corals and red calcareous algae. However, unlike modern reefs, micrite makes up the vast majority of the internal sediment, suggesting a development into a low-energy environment. Compared to Upper Paleocene coral boundstones, those from the Lower Paleocene of Maiella display a higher abundance of corals, suggesting a reduction in coral carbonate production during the Late Paleocene. This decline is also reflected by a period of scarcity of coral-dominated facies throughout the Tethys, starting from the latest Paleocene and extending till the end of the Middle Eocene. This can be connected to global temperatures, which rise in the Thanetian and remain relatively high till the end of the Middle Eocene, however, other factors most likely played a role. The quantitative analysis of the skeletal assemblage turns out to be a useful instrument for tracking the effect of environmental changes. Further data, especially from long and extensive successions of neritic carbonates such as those of Maiella, may help in disentangling the effects of the other environmental variables.
Keywords: Reefs; calcareous algae; rudists; shallow-water carbonates; Late Cretaceous; Danian; Thanetian.